2005
DOI: 10.1016/j.femsyr.2004.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and genome-wide transcriptional responses of to high carbon dioxide concentrations

Abstract: Physiological effects of carbon dioxide and impact on genome-wide transcript profiles were analysed in chemostat cultures of Saccharomyces cerevisiae. In anaerobic, glucose-limited chemostat cultures grown at atmospheric pressure, cultivation under CO(2)-saturated conditions had only a marginal (<10%) impact on the biomass yield. Conversely, a 25% decrease of the biomass yield was found in aerobic, glucose-limited chemostat cultures aerated with a mixture of 79% CO(2) and 21% O(2). This observation indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 65 publications
4
44
1
Order By: Relevance
“…Technology is now available to determine the genome-wide transcriptional response of yeast to environmental changes and has been used to elucidate the transcriptional response to a number of brewery-relevant parameters, including, for example, availability of oxygen and anaerobiosis (Aguilera et al, 2005;Lai et al, 2005), ageing (Fabrizio et al, 2005;Laun et al, 2005), dehydration and hydration (Singh et al, 2005), ethanol toxicity (Alexandre et al, 2001;Caba et al, 2005;Fujita et al, 2006;van Voorst et al, 2006), glucose repression and diauxic shift (DeRisi et al, 1997;Griffin et al, 2002), nutrient limitation (Causton et al, 2001;Gasch et al, 2000), osmotic stress (Gasch et al, 2000), oxidative stress (Causton et al, 2001;Gasch et al, 2000;Koerkamp et al, 2002), pH (Causton et al, 2001), salt stress (Caba et al, 2005), sugar stress (Ando et al, 2006;Erasmus et al, 2003) and temperature change (Causton et al, 2001;Gasch et al, 2000;Homma et al, 2003;Sahara et al, 2002). However, very few studies have utilized production strains of yeast or have involved incubation in brewery wort (Smart, 2007).…”
Section: B R Gibson Et Almentioning
confidence: 99%
“…Technology is now available to determine the genome-wide transcriptional response of yeast to environmental changes and has been used to elucidate the transcriptional response to a number of brewery-relevant parameters, including, for example, availability of oxygen and anaerobiosis (Aguilera et al, 2005;Lai et al, 2005), ageing (Fabrizio et al, 2005;Laun et al, 2005), dehydration and hydration (Singh et al, 2005), ethanol toxicity (Alexandre et al, 2001;Caba et al, 2005;Fujita et al, 2006;van Voorst et al, 2006), glucose repression and diauxic shift (DeRisi et al, 1997;Griffin et al, 2002), nutrient limitation (Causton et al, 2001;Gasch et al, 2000), osmotic stress (Gasch et al, 2000), oxidative stress (Causton et al, 2001;Gasch et al, 2000;Koerkamp et al, 2002), pH (Causton et al, 2001), salt stress (Caba et al, 2005), sugar stress (Ando et al, 2006;Erasmus et al, 2003) and temperature change (Causton et al, 2001;Gasch et al, 2000;Homma et al, 2003;Sahara et al, 2002). However, very few studies have utilized production strains of yeast or have involved incubation in brewery wort (Smart, 2007).…”
Section: B R Gibson Et Almentioning
confidence: 99%
“…The expression of fungal CA reflects this importance as CAs are strongly induced in an environment scarce in CO 2 compared to hypercapnic conditions. 6,10,13,15,16 We recently established that fungal CA induction in C. albicans in low CO 2 is controlled by Rca1p, a 32 kDa transcription factor with a basic leucine zipper (bZIP) domain in its C-terminus. We extended this observation to the model organism S. cerevisiae where the Rca1p ortholog, Cst6p, exhibits an identical function.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the combination of high-gravity brewing with other modern practices, such as the use of tall cylindroconical fermenters, results in increased hydrostatic pressure and carbon dioxide levels and decreased oxygen levels. Recently it was shown that fungal adenylate cyclases function as CO 2 sensors (1,3,22,24). Thus, different levels of CO 2 may influence yeast fermentation, as there is a direct link between adenylate cyclase activity and glycolysis (13,26).…”
mentioning
confidence: 99%